Os significados da alfabetização e do letramento para adultos e alfabetizados - Iara Silva Lucio (2007)
This research had as objective to discuss the interruption of the schooling process at EJA analysing the expectations and understanding that egress students of the Education for Young and Adults project have in terms of literacy We analyzed the participants view of illiteracy with a focus on the epresentations of the understanding of being illiterate in a major urban area and further analyzed the acquisition of reading and writing skills as condition o he interruption of the schooling process. This study required the adoption o ethnographic survey instruments that allowed a large volume of data to be assessed and from its analysis the study could investigate participants perception of what is to be illiterate / literate, but above all, to reflect about the effects of literacy namely, the implications of the acquisition of the writing anguage in theirs own lives and in the lives of the people associated with them There was the understanding that the participants shared the desire of learning o read and to write in order to deal with daily life independently and the nclusion of a formal learning of the writing word in different times of theirs lives meant an ability to participate in events and practices of literacy without the need of help from others. We believe that each participant left the EJA projec because, from their point of view, there was a conclusion of a process, in othe words, the subjects had established that from that moment they had become iterate subjects. One of the big challenge that the research imposes is to offer n a highlited context for a great number of initiatives directed to EJA educational opportunities to develop adults literacy. And to offer the opportunities, firstly, is necessary to know the real demands of illiterate adults and newly-literate ones have in relation to the acquisition of the writing ability in addition to understanding how they perceive themselves as EJA subjects.